[PP.15.23] CLINICAL CHARASTERISTICS, OFFICE BLOOD PRESSURE, MEDICAL THERAPY AND CARDIAC STRUCTURE IN SUBJECTS WITH SUSPECTED DRUG-RESISTANT HYPERTENSION REFERRED TO HYPERTENSION CLINIC. (September 2017) - Malek, F.; Vondrakova, D.; Dvorak, J.; Neuzil, P.
Abstract : Objective: Backround: patients with suspected drug-resistant hypertension referred for non-pharmacological treatment are usualy not on optimal medical therapy Study objective: to analyse blood pressure control and composition of medical therapy in patients referred to hypertension clinic with suspected drug-resistant hypertension Design and method: Patients and methods: group of 60 consecutive patients (34 males, 26 females, mean age 66 years) and mean BMI 30 kg/m 2 with suspected drug-resistant esential underwent BP office recording, laboratory examination and echocardiographic study same date in hypertension clinic. Patients had significant comorbidities: coronary artery disease 27%, dyslipidaemia had 88%, DM 57% and 78% were smokers. Office blood pressure was measured with automatic BP monitor Omron M6 after 5 minutes rest, mean value of three recordings was used. Medical therapy was analysed from patients records. Dual mode, Pulse-Doppler and Tissue Doppler Imaging were used for the assessment of: cardiac chambers size, left ventricular (LV) ejection fraction, calculation of LV mass index (LVMI) and RWT (relative wall thickness). Results: Mean systolic office BP was 146.8 mmHg and diastolic 86.9, with 82% patients above target sBP (140 or 130) and 53% (90 or 80) above target dBP. Total number of 37 (62%) patients were receiving ACEIs, 30% ARBs, 48% CCBs and 60% thiazide or thiazide –like diuretics, 65% patients were on BBs and 13% on spironolactone. Mean number of antihypertensive drugs was 3.4. Mean LVMI was 85, 5 g/m 2 and RWT 0, 40 with only 18% male patients above LVMI upper normal limit (> 102 g/m 2 ) and 19% females above 88 g/m 2 and 37% subjects above RWT upper normal limit. Conclusions: Patients referred to tertiary care hypertension clinic are not on optimal medical therapy, low proportion of patients are treated with diuretics and spironolacton, high number are treated with betablockers. Despite not optimal therapy and BP control, only small number of patients had parameters of cardiac hypertrophy. Supported by Ministry of Health, Czech Republic - conceptual development of research organization (Nemocnice Na Homolce – NNH, 00023884), IG 150505.